Do Environmental Innovations, Trade and Economic Growth Affect the Ecological Footprint in Industrialized Countries? Panel Augmented Mean Group and Common Correlated Effect Estimations - Akyol, Mehmet; Soyyigit, Semanur (International Journal of Economics, Management and Accounting, 2025)
This study assessed the environmental technological innovation (ETI) of the 13 countries with the highest industrial added value (China, the United States, Japan, Germany, India, the United Kingdom, South Korea, France, Russia, Italy, Mexico, Brazil, Indonesia) over the period between 1992 and 2019. The objective is to evaluate the impact of carbon dioxide (CO?) emissions, trade openness (TO), and economic growth (EG) on the ecological footprint (EFP). In this study, a panel data analysis was conducted utilizing the second-generation PANIC unit root test, the Westerlund cointegration test, the Dumitrescu-Hurlin causality test, and the common correlated effect mean group (CCEMG) and augmented mean group (AMG) estimator methods. The results of the analysis demonstrate that, according to the CCEMG, ETI exerts a mitigating influence on EFP in Indonesia. In numerous countries, CO2 has been observed to increase EFP, whereas in a select few countries, EG has been found to have a similar effect. Conversely, in China and South Korea, TO has been identified as a factor contributing to an increase in EFP, while in the United States, it has been identified as a factor that contributes to a decrease in EFP. The AMG indicates that ETI results in a decrease in EFP in Brazil and Indonesia, while simultaneously producing an increase in Mexico. While CO2 is observed to increase EFP in numerous countries, EG is seen to increase EFP in many countries, although this is only the case in India. TO is found to decrease EFP in China, India, South Korea, and Brazil, while simultaneously increasing it in Germany. The empirical evidence suggests that policies aimed at limiting uncontrolled economic growth, prioritising environmentally friendly technological innovations, improving international trade processes and policies with the objective of reducing emissions, and developing environmentally friendly processes and products in production are likely to be effective.